2023
DOI: 10.1177/00472875231182109
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Customer Engagement in Sustaining Subjective Well-being After a Travel Experience: Findings From a Three-Wave Study

Abstract: Although customer engagement’s (CE) effects on marketing-related outcomes are well documented, its broader impacts on life domain constructs (e.g., subjective well-being [SWB]) have received less attention. We propose CE as a viable mechanism for prolonging travel’s positive effects on SWB. Specifically, this study adopts a three-wave design to investigate the linkages between destination brand experience (DBE), CE, and SWB over time. Our results indicate that sensory destination experience ( t1) and affective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 181 publications
0
4
0
Order By: Relevance
“…Their study highlighted the positive effects of wellness motivation on two engagement factors. So, Li, and Kim [ 43 ] conducted a systematic literature review and found that motivation leads to engagement at cultural and heritage sites and travel destinations for special-interest destinations.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Their study highlighted the positive effects of wellness motivation on two engagement factors. So, Li, and Kim [ 43 ] conducted a systematic literature review and found that motivation leads to engagement at cultural and heritage sites and travel destinations for special-interest destinations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Specifically, previous research found partial mediating effects between engagement, satisfaction, and destination loyalty [ 47 ]. Destination brand engagement positively affects tourists’ destination recommendation intentions and intentions to revisit [ 41 , 43 , 46 , 55 , 56 ]. Therefore, we propose that two engagement constructs positively influence satisfaction and destination loyalty.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This study concerns tourism, a context in which consumers primarily engage with related services to fulfill hedonic (e.g., fun/entertainment) uses‐and‐gratifications–informed needs (Hollebeek, 2013; So, Kim, et al, 2021). Even though one's immediate post ‐travel recall of trip‐related excitement tends to be high, this feeling is apt to decline as time passes (So et al, 2023). This finding has ample implications.…”
Section: Implications Limitations and Future Researchmentioning
confidence: 99%
“…This approach can uncover whether variables themselves or other factors contribute to developmental trajectories (e.g., in customers' perceptions) and interacting processes over time (Grammer et al, 2013; White & Arzi, 2005). Longitudinal data also allow researchers to capture constructs' temporal precedence (e.g., Selig & Little, 2012; So et al, 2023), thus clarifying potential causal relationships and how effects apply across time (Mora Cortez & Ghosh Dastidar, 2022). As such, we employ an autoregressive cross‐lagged panel model to measure how one construct (i.e., engagement) affects another (e.g., stickiness) at a later point (Selig & Little, 2012).…”
Section: Introductionmentioning
confidence: 99%